Tourist Behavior and Demand for Digital Disconnection: A Review - González-Padilla, Paula (Journal of Tourism, Sustainability and Well-being, 2022)
The hyper digitization of the current moment has led to the emergence of new behaviors and trends such as the one that occupies the object of study of this research about vacations free of digital media. The main objective is to shed light on a subject that has been little explored but is already present and future in the tourism sector. In this study, it is intended to classify and find the main motivations of tourists to take this type of vacation and see the relationship of this trend with today’s environmental awareness. To meet the objectives, a systematic literature review is carried out from which the 3 main motivations that drive this type of disconnection tourism are constructed: nature and authenticity, reconnecting with oneself, and the search for human connection.